Scriptwork : a director's approach to new play development - Kahn, David, 1955- (Southern Illinois University Press, 1995)
Despite the popular myth that plays arrive at the theatre fully formed and ready for production, the truth is that for centuries, most scripts have been developed through a collaborative process in rehearsal and in concert with other theatre artists. David Kahn and Donna Breed provide the first codified approach to this time-honored method of play development, with a flexible methodology that takes into account differing environments and various stages of formation.